HUBUNGAN ANEMIA, STATUS GIZI, OLAHRAGA DAN PENGETAHUAN DENGAN KEJADIAN DISMENORE PADA REMAJA PUTRI: RELATIONSHIP OF ANEMIA, NUTRITIONAL STATUS, SPORT AND KNOWLEDGE WITH THE EVENT OF DYMENORORE IN ADOLESCENT WOMEN - Cholifah, Cholifah; Hadikasari, Alfinda Ayu (Jurnal Kebidanan Midwiferia, 2015)
Based on data from adolescent in Study Program D3 of Midwifery Muhammadiyah Sidoarjo University, the incident of dismenore is high enough amounts 85 %. The purpose of the Research to know the relation of anemia, nutrient status, knowledge and sport with dismenore at adolescent.The research design was analytic survey and the method use cross sectional. Data was used primary data and was get from kuesioner. The sample were 81 adolescent in Study Program D3 of Midwifery Muhammadiyah Sidoarjo University. Sample was taken with simple random sampling and will presented in frequency and crosswise, and than will analyze with Exact Fisher Test.The Research result showed that majority of age was 19 yeasrs old (61,73%) get anemia (70,37%), normal nutrient status (54,32%), do not do sport (87,65% ) knowledge is less (91,3%)and dismenore(87,65%). Exact Fisher Test result was done in anemia, nutrient status, sport and knowledge variables show that P (anemia) = 0,006, P (nutrient status) = 0,023, P(sport) = 0,0001 and P (knowledge) = 0,016 with the result that P < 0,05 so Ho was rejected. There was relation between anemia nutrient status sport and knowledge with dismenore.